What Horses and Humans See: A Comparative Review. (5th March 2009) - Murphy, Jack; Hall, Carol; Arkins, Sean
Abstract : Adaptations of the mammalian eye have tailored each to its own particular ecological niche. On the one hand, it would appear that the horse is best served by a system that can keep "half an eye" on everything, while the human benefits from focussing on more specific aspects of the visual array. By adapting a range of techniques, originally used to assess human visual ability, it has been possible to compare the human visual experience with that of the horse. In general, the results of the majority of these comparative studies indicate that the visual capabilities of the horse are broadly inferior to the human equivalents in acuity, accommodation, and colour vision. However, both the horse and human abilities to judge distance and depth perception may be quite comparable while equine vision is certainly superior to that of human's under scotopic conditions. Individual variation in visual ability, which is routinely taken for granted in humans, is also likely to occur in the horse. Such variation would undoubtedly affect equine performance, particularly in terms of expectation of athletic competitive outcomes in modern equitation. In addition to such considerations as conformation and athletic ability, a detailed assessment of the visual ability might contribute to a more accurate prediction of future performance characteristics in the horse. Although further investigation is required in order to appreciate fully both the capabilities and limitations of the equine visual system, the information currently available should now be considered and applied more rigorously both in the design of the equine environment and in the implementation of contemporary equine training methods. This need is the greatest in areas of equestrian sport where the outcomes of either or both equine and human visual judgements can be critical, the cost of failure often high and occasionally results in fatal consequences for both parties of the horse-human dyad.